2016
DOI: 10.1155/2016/2106756
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis Methods of CoFe2O4and Ag-CoFe2O4Nanoparticles Using Hibiscus Extracts and Their Antimicrobial Potential

Abstract: The cobalt ferrite (CoFe2O4) and silver-cobalt ferrite (Ag-CoFe2O4) nanoparticles were obtained through self-combustion and wet ferritization methods using aqueous extracts ofHibiscus rosa-sinensisflower and leaf. X-ray diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy, and magnetic measurements were used for the characterization of the obtained oxide powders. The antimicrobial activity of the cobalt ferrite and silver-cobalt ferrite nanoparticles against Gram-positive and Gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 33 publications
1
34
0
3
Order By: Relevance
“…Along with the plant and leaf extracts, the extracts of flowers, fruits, peels, and seeds have been explored as fuel in combustion process for the synthesis of metal oxides. Gingasu et al., compared the effect of Hibiscus rosa‐sinensis flower and leaf extracts as the fuel in combustion process for the synthesis of CoFe 2 O 4 and Ag‐CoFe 2 O 4 nanoparticles. The crystalline size of the CoFe 2 O 4 particles synthesised using hibiscus flower extract was found to have 10 nm and 18 nm respectively for as synthesised and calcined at 800 °C.…”
Section: Plant Based Renewable Fuels In Combustion Processmentioning
confidence: 99%
“…Along with the plant and leaf extracts, the extracts of flowers, fruits, peels, and seeds have been explored as fuel in combustion process for the synthesis of metal oxides. Gingasu et al., compared the effect of Hibiscus rosa‐sinensis flower and leaf extracts as the fuel in combustion process for the synthesis of CoFe 2 O 4 and Ag‐CoFe 2 O 4 nanoparticles. The crystalline size of the CoFe 2 O 4 particles synthesised using hibiscus flower extract was found to have 10 nm and 18 nm respectively for as synthesised and calcined at 800 °C.…”
Section: Plant Based Renewable Fuels In Combustion Processmentioning
confidence: 99%
“…Nanopartikel spinel ferrit mempunyai rumus struktur MFe2O4 (M= Mn 2+, Co 2+, , Fe 2+, , Ni 2+, , Mg 2+ , Cu 2+, , Zn 2+, ) dengan struktur kristal kubik spinel (Iranmanesh et al 2017), memiliki rasio luas permukaan yang besar terhadap volume dan sifat magnetik yang unik seperti koersivitas tinggi, magnetisasi sedang, pemfilteran spin, dan efek domain tunggal. Aplikasi spinel ferrit dari jenis MFe2O4 telah menarik perhatian peneliti selama beberapa dekade, seperti perekaman magnetik, penyimpanan energi magnetik, katalisis, biomedis, dan pengolahan air limbah (Gingasu et al 2016). Di antara nanopartikel magnetik, MnFe2O4 adalah kelompok bahan spinel ferrit lunak dengan luas permukaan yang tinggi, permeabilitas magnetik tinggi, dan ketahanan listrik tinggi (Kafshgari et al 2018).…”
Section: Pendahuluanunclassified
“…Ekstrak tumbuhan mengandung berbagai metabolit termasuk karbohidrat, polisakarida, fenol, asam amino, dan vitamin, yang dapat bertindak sebagai capping agent. Penggunaan ekstrak tumbuhan dalam sintesis dapat mempengaruhi ukuran, bentuk, dan morfologi nanopartikel (Gingasu at al. 2016).…”
Section: Pendahuluanunclassified
“…The nanoparticles were suspended in dimethyl sulfoxide (DMSO) to prepare a stock solution of 20 mg/mL concentration. Gingasu et al [22] have shown that DMSO does not show any activity against the test organisms except for Escherichia coli where partial inhibition of its growth was recorded. Agar well diffusion method was used for the antibacterial activity determination.…”
Section: Antimicrobial Studymentioning
confidence: 99%